2015
DOI: 10.7150/ijms.11343
|View full text |Cite
|
Sign up to set email alerts
|

Using Vascular Closure Devices Following Out-Of-Hospital Cardiac Arrest?

Abstract: Objectives and Background: Despite a generally broad use of vascular closure devices (VCDs), it remains unclear whether they can also be used in victims from out-of-hospital cardiac arrest (OHCA) treated with mild therapeutic hypothermia (MTH).Methods: All victims from OHCA who received immediate coronary angiography after OHCA between January 1st 2008 and December 31st 2013 were included in this study. The operator decided to either use a VCD (Angio-Seal™) or manual compression for femoral artery puncture. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…After removing 462 duplicate studies, step by step screening was performed based on inclusion and exclusion criteria. Eventually, 32 studies comprising 12 RCTs [28][29][30][31][32][33][34][35][36][37][38][39], 17 observational studies [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], and 3 propensity-score matched studies [56][57][58] were included in this meta-analysis. Figure 1 shows the flowchart of inclusions and exclusions.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing 462 duplicate studies, step by step screening was performed based on inclusion and exclusion criteria. Eventually, 32 studies comprising 12 RCTs [28][29][30][31][32][33][34][35][36][37][38][39], 17 observational studies [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], and 3 propensity-score matched studies [56][57][58] were included in this meta-analysis. Figure 1 shows the flowchart of inclusions and exclusions.…”
Section: Search Resultsmentioning
confidence: 99%
“…Vascular complication is the focus of attention and the most controversial issue. Previous researches have suggested that VCDs may lead to an increase in femoral artery thrombosis, arteriovenous fistula, pseudoaneurysm, and other adverse events [ 29 , 42 , 43 ]. However, the results of this meta-analysis showed that VCDs did not cause additional injury and may even improve the severity of complications.…”
Section: Discussionmentioning
confidence: 99%
“…They provide improved patient comfort and decreased time to ambulation (5). However, their impact on vascular complications is, at best, no different than manual compression and in some cases, possibly even worse 5 - 7 . The degree of uncertainty in VCD use is further aggravated by the fact, that our knowledge is based on few randomized studies and that these studies were mostly conducted in the setting of diagnostic procedures 5 .…”
Section: Introductionmentioning
confidence: 99%